Designing Social Interactions with a Humorous Robot Photographer - Adamson, Timothy; Lyng-Olsen, C. Burton; Umstattd, Kendrick; Vázquez, Marynel (2020 15th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2020)
This paper describes our efforts to explore the design space of social interactions for a robot portrait photographer. Our human-centered design process involved professional and amateur photographers to better understand the social dimensions of subject-photographer interactions. This exploration then guided our design of a robot photographer, which employs humor to elicit spontaneous smiles during photography events. In a laboratory evaluation of our robot prototype, we found that the majority of the subjects considered the robot's humor to be comical and appreciated it. More spontaneous smiles were elicited by the robot when it delivered humorous content to its subjects than when it was not humorous. Our findings provide insights for the design of future social robot photographers.